1997
DOI: 10.1007/s002469900118
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Intermittent Tachyarrhythmias in the Fetus

Abstract: Persistent fetal tachycardias are known to have an adverse effect on fetal outcome. The outcomes of intermittent fetal tachyarrhythmias over a 12-year period at a tertiary fetal cardiology center were studied. Main outcome criteria included control of arrhythmia and death during the prenatal or postnatal period. A total of 28 fetuses had an intermittent tachyarrhythmia: 4 had intermittent atrial flutter and 24 had supraventricular tachycardia. At the time of presentation 14 fetuses were hydropic, and in 5 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Guntheroth et al (1996) reported no cases of fetal hydrops when the rate of SVT was less than 230 beats/min. Other authors have found no relationship between rate or duration of SVT and risk of fetal hydrops, which has been reported even in the presence of intermittent SVT (Simpson and Sharland 1998;Simpson et al 1997). Two recent series suggested a greater risk of heart failure when sustained STV occurs at an earlier gestational age (Cuneo and Strasburger 2000;Naheed et al1996).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Guntheroth et al (1996) reported no cases of fetal hydrops when the rate of SVT was less than 230 beats/min. Other authors have found no relationship between rate or duration of SVT and risk of fetal hydrops, which has been reported even in the presence of intermittent SVT (Simpson and Sharland 1998;Simpson et al 1997). Two recent series suggested a greater risk of heart failure when sustained STV occurs at an earlier gestational age (Cuneo and Strasburger 2000;Naheed et al1996).…”
Section: Discussionmentioning
confidence: 95%
“…Two recent series suggested a greater risk of heart failure when sustained STV occurs at an earlier gestational age (Cuneo and Strasburger 2000;Naheed et al1996). Spontaneous resolution of SVT can occur in utero, during delivery or in the neonatal period (Simpson and Sharland 1998;Simpson et al 1997;Cuneo and Strasburger 2000;Bergmans et al 1995). Appropriate management of SVT should be tailored to the individual case.…”
Section: Discussionmentioning
confidence: 96%
“…However, fetal tachyarrhythmia, if untreated, can result in 8% to 30% of fetal and neonatal mortality, and early delivery of an untreated preterm and hydropic infant with tachycardia has unacceptable morbidity and mortality [1][2][3][4][5][6]12,15]. These are compelling reasons to treat fetal tachyarrhythmia.…”
Section: Treatmentmentioning
confidence: 96%
“…They are defined as a fetal heart rate ≥ 180 bpm [2], but most often are in excess of 200 bpm [4]. Although sustained tachycardia (present ≥ 12 consecutive hours) [5] has been known to be a risk factor for fetal congestive heart failure [3], intermittent tachycardias can also be associated with hydrops [6]. The majority of fetal tachycardias are due to supraventricular tachycardia (SVT), which shows 1:1 atrioventricular (AV) contraction sequence, abrupt onset and termination, and minimal (within 10 bpm range) or no heart rate variability.…”
Section: Introductionmentioning
confidence: 99%
“…Several life-threatening arrhythmias attack the fetus paroxysmally [3], and thus it may be unsatisfactory to record FMCG for a short duration. There are several obstacles in long-duration FMCG such as fetal movement, pregnant women's lower back pains in late gestation [4,5], and supine hypotensive symptoms [6].…”
Section: Introductionmentioning
confidence: 99%